Governance in rural China: an ethnographic case study in two suburban villages in Guangdong Province, China - Li, Jinliang (2017)
This PhD research focuses on rural governance in the context of Mainland China. It focuses on three aspects of the changing rural governance: 1) internalization of the state-sponsored reforms for rural democratization, 2) external intervention and mediation of the human agents for policy implementation, and 3) dispute settlement. Drawing upon the three above-mentioned aspects, this study aims to dissect the interactive processes of China’s rural governance over the ongoing urbanisation of small-to-medium-sized cities. The fieldwork utilizes iterative-inductive ethnography as the research methodology. It additionally adopts the theoretical framework of social constructionism and actor-oriented perspectives to interpret the changing rural governance and employs interface analysis to examine the ethnographic data. It finds that the outcome of rural governance in the selected villages is greatly influenced by the interaction of the human agents’ capabilities and the (emerging) structural forces. In particular, various actors not only construct the emerging power structure but make use of their own knowledge, power relations, discursive practices, and innovate strategies to accommodate, negotiate and compromise with the external forces to solve problems emerging out of rural governance. Simultaneously, structural factors limit the scope of the actors’ choices, and the opportunities for strategies concerning rural governance. In terms of the representativeness of the selected samples, it firstly could reflect on the possible trajectories of rural governance over the next decade for the urbanisation of small-to-medium-sized cities, which is promoted by both the central and local governments. Secondly, the selected samples represent the changing rural governance in villages that feature Hakka culture and history. Further research should be taken on villages consisting of different cultural contexts and political-economic conditions in order to expand on this research as the representativeness of the samples is limited to the specific contexts under study.